Knowledge, attitudes, beliefs and practices (KABP) concerning family planning among urban male high school students in the Zwelitsha District, Ciskei - Kwaw, William Bangoto (Department of Paediatrics and Child Health, 2017)
It takes two to tango! However, family planning programmes in most countries especially in Sub-Saharan Africa have focused almost solely on one - the female-invariably with little impact. The few attempts which have been made to involve males have concentrated on the adult male. It was felt the time had come to involve the adolescent males most of whom are already sexually active and after all are the husbands and fathers of tomorrow. Male high school students (N=240) out of a total of 2101 male students were randomly selected from all the six urban high schools in the Zwelitsha District of Ciskei (now part of the new Eastern Cape Province of RSA) and were surveyed to obtain information on KABP concerning family planning. The study was undertaken to provide information for planning of a family planning health intervention programme by the school health team in an attempt to address the high unplanned teenage pregnancy rate and STDs in the schools. The response rate was 83,3%. Important findings included the following: 90% reported they had already had sexual intercourse; the mean age at first sexual intercourse was 15.4 years; the interval from first intercourse to first contraceptive use was 2 years; knowledge of contraceptives was at times scanty and there were several misconceptions and myths concerning fertility, contraceptives and STDs; majority (71,5%) felt the decision to use contraceptives should be the responsibility of both male and female; 86,4% expressed the desire to use contraceptives in the future and 73,0% felt sex education should start in primary school. The adolescent male is interested in family planning and wants to be an active participant in the programme. Recommendations for improved family planning services in schools are made.